KEHAMILAN REMAJA TERHADAP KEJADIAN ANEMIA DI WILAYAH PUSKESMAS CEMPAKA KOTA BANJARBARU - Hapisah Hapisah; Ahmad Rizani (Jurnal Vokasi Kesehatan, 2015)
Abstract: The Correlation Of Teenage Pregnancy With Anemia In Region Cempaka Health Centers Banjarbaru. The purpose of research is to know the correlation of teenage pregnancy with anemia in regional Cempaka Health Centers Banjarbaru. The research is using the design of survey analyzing with the cross-sectional approach. The population is all of the pregnant women in working area of Cempaka Health Centers Banjarbaru from January to July in 2013 is 382 people with the sample is 80 people. The sampling uses Random sampling with (systematic sampling). The result of research showed 18 people (22.5%) respondent with teenage pregnancy, respondent have anemia during pregnancy is 31 people (38.75%) and there is a correlation between teenage pregnancy with anemia cases, the result of Chi-Square test showed the value of p = 0.013 < α = 0.05.